Superior Islamic Education System in Islamic Junior Hight School - Hakim, Abdul; Warisno, Andi; Ansori, Afif; Andari, An An (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this research is to find out the superior Islamic education delivery system at MTsN 2 Bandar Lampung. This research method is a case study qualitative research. Data were obtained through interviews, documentation, and observation at MTs N 2 Bandar Lampung. Sources of interview data were obtained from school principals and curriculum deputy heads. Observations were made by direct observation at MTs N 2 Bandar Lampung and documentation by reviewing curricula and documents regarding the delivery of superior Islamic education. The results of the study concluded that the superior class at MTs N 2 Bandar Lampung was a class containing selected students who were selected based on strict conditions, namely academic potential, IQ, and student creativity which were adequate. The maintenance system is carried out by doing recruitment which consists of 2 paths, namely the achievement path and the regular path. Specifically, there are 3 (three) components of the superior program implemented in the superior class of MTs Negeri 2 Bandar Lampung, namely Academic Excellence, Moral Excellence, and Skill Excellence. Each component has special programs. Each component of the excellence program is expected to produce students who excel in their respective fields.